STUDENTS’ SCIENCE LITERACY ABILITY PROFILE IN ENVIRONMENTAL POLLUTION AND GLOBAL WARMING MATERIAL - Laela Ulfa; Rusilowati A; Nugroho S.E (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2017)
This research head for measure profile of students’ science literacy ability in environmental pollution and global warming material. The study was conducted in one of SMP Negeri Semarang with samples of 70 students from grade VII D and VII E. The profile of literacy science of students from the highest percentage till the lowest was science as a body of a knowledge was 70,36%, science as a way of thinking was 61,71%, the interaction between science, technology, and society was 61,43% categorized enough level, and science as a way for investigating was 38,21 categorized too less.keywords: science literacy, scince literacy ability